On the existence of the solution of Burgers' equation for n≤4 - Adel N. Boules (International Journal of Mathematics and Mathematical Sciences)
In this paper a proof of the existence of the solution of Burgers' equation for n≤4 is presented. The technique used is shown to be valid for equations with more general types of nonlinearities than is present in Burgers' equation.